Case series of paediatric adnexal torsion: rare yet urgent entity - Mishra, Vineet; Hokabaj, Shaheen; Roy, Priyankur; Aggarwal, Rohina; Vyas, Bhumika; Mehta, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Ovarian torsion is a true emergency which warrants early diagnosis and timely surgical management to avoid the catastrophic consequences of further adnexal injury. In paediatric population, this is especially dangerous as the condition can go undiagnosed because of its rarity and nonspecific presentation of disease. This leads to delay in surgical exploration and loss of ovarian function. We encountered 6 cases of ovarian torsion in paediatric age group during a period of 2 years, at a tertiary care hospital in Ahmedabad. After enquiry of the symptoms and a series of investigations, a provisional diagnosis of torsion ovary was made and they were taken up for surgery. Intra-operatively all the patients were found to have non-salvageable ovary and fallopian tube on the affected side, and subsequently they underwent salpingo-oophorectomy. Diagnosis of ovarian torsion requires clinician awareness and a high degree of suspicion. Conservative surgery, in the form of ovarian detorsion can be tried in cases of ischemia but if ovarian necrosis has occurred, then salpingo-oophorectomy is performed as the last resort.